Предмет: Алгебра,
автор: prostttt
Полное решение! Спасибо заранее
Приложения:
Ответы
Автор ответа:
1
7)
(28a/(16a²-b²))-(7/(4a+b))=(28a/((4a-b)(4a+b)))-(7/(4a+b))=(28a-7(4a-b))/((4a-b)(4a+b))=(7b)/((4a-b)(4a+b))=42/((8-6)·14)=42/28=1,5
8)-3(2+2x)-3x≤2
-6-6x-3x-2≤0
9x+8≥0
x≥-8/9
ответ 3
(28a/(16a²-b²))-(7/(4a+b))=(28a/((4a-b)(4a+b)))-(7/(4a+b))=(28a-7(4a-b))/((4a-b)(4a+b))=(7b)/((4a-b)(4a+b))=42/((8-6)·14)=42/28=1,5
8)-3(2+2x)-3x≤2
-6-6x-3x-2≤0
9x+8≥0
x≥-8/9
ответ 3
Похожие вопросы
Предмет: Русский язык,
автор: Solneliiko9967
Предмет: Русский язык,
автор: DauncherGames
Предмет: Русский язык,
автор: Nastyaizh6178
Предмет: Алгебра,
автор: dcherepaxa
Предмет: Химия,
автор: Oleg19851